Predicting Pyrolysis Products of PE, PP, and PET Using NRTL Activity Coefficient Model - Seyed Mousa FakhrHoseini; Majid Dastanian (Journal of Chemistry)
Using thermodynamic models is a desired method for predicting an equilibrium when occurring in a system. If a thermodynamic model can predict an equilibrium condition in a pyrolysis, for a new way will be open for scientists in predicting equilibrium in a reaction without need to kinetic models. In this work, low-density polyethylene, polypropylene, and polyethylene terephthalate were used instead of feed of pyrolysis process. The process was maintained at 500°C with 5 different temperature raising ratios 6, 8, 10, 12, and 14. Then the process was modeled thermodynamically using NRTL activity coefficient model. Using this model, the binary interaction coefficients were investigated for the system of “char, oil, and gas.” Results showed that polyethylene and polypropylene produced the maximum liquid product. Calculated RMSD objective function was 0.0157; that it is acceptable for this process.